Defective function of GABA-containing synaptic vesicles in mice lacking the AP-3B clathrin adaptor - Nakatsu, Fubito (The Rockefeller University Press, 2004)
AP-3 is a member of the adaptor protein (AP) complex family that regulates the vesicular transport of cargo proteins in the secretory and endocytic pathways. There are two isoforms of AP-3: the ubiquitously expressed AP-3A and the neuron-specific AP-3B. Although the physiological role of AP-3A has recently been elucidated, that of AP-3B remains unsolved. To address this question, we generated mice lacking μ3B, a subunit of AP-3B. μ3B−/− mice suffered from spontaneous epileptic seizures. Morphological abnormalities were observed at synapses in these mice. Biochemical studies demonstrated the impairment of γ-aminobutyric acid (GABA) release because of, at least in part, the reduction of vesicular GABA transporter in μ3B−/− mice. This facilitated the induction of long-term potentiation in the hippocampus and the abnormal propagation of neuronal excitability via the temporoammonic pathway. Thus, AP-3B plays a critical role in the normal formation and function of a subset of synaptic vesicles. This work adds a new aspect to the pathogenesis of epilepsy.